Efficacy of Liuzijue Qigong in patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis. (May 2022) - Xu, Shuanglan; Zhang, Dandan; He, Quan; Ma, Chenhui; Ye, Sheng; Ge, Linyang; Zhang, Liuchao; Liu, Weihua; Chen, Zi; Zhou, Linfu
Abstract: Background: Liuzijue is a traditional Qigong exercise that is commonly performed in China. However, the treatment effects of Liuzijue Qigong are controversial. The aim of this systematic review was to evaluate the efficacy of Liuzijue Qigong in patients with chronic obstructive pulmonary disease (COPD). Methods: Randomised controlled trials were identified by searching several English and Chinese databases from inception to August 8, 2020. Study selection and data extraction were independently performed by two investigators. Data synthesis and analysis were carried out with Review Manager software 5.2. Quality assessment for each study was based on the modified Jadad scale. Results: Forty studies with 3137 participants were included. Significant improvements were observed in the following outcomes (mean difference, 95% confidence interval): forced expiratory volume in 1 s (0.17, 0.09–0.25) and its percent predicted normal value (6.04, 3.43–8.65), forced expiratory volume in 1 s to forced volume capacity ratio (6.95, 3.06–10.83), 6-min walking distance (33.06, 23.73–42.38), 30-s sit-to-stand test (2.65, 0.98–4.32), COPD assessment test score (− 2.04, − 2.77 to − 1.30), modified Medical Research Council dyspnea scale (− 0.34, − 0.48 to − 0.20), Medical Research Council dyspnea scale (− 0.37, − 0.57 to − 0.18), Traditional Chinese Medicine syndrome score (− 1.85, − 2.86 to − 0.85), Hamilton Anxiety Scale (− 2.31, − 3.04 to − 1.59), Hamilton Depression Scale (− 2.08, − 2.45 to − 1.71) and St. George's Respiratory Questionnaire (− 6.94, − 9.20 to − 4.67). Conclusions: Liuzijue Qigong may be an effective adjuvant therapy for the improvement of lung function, exercise capacity, health status, mental status and quality of life in patients with COPD . Highlights: Forty articles were identified to evaluate the efficacy of Liuzijue Qigong in patients with chronic obstructive pulmonary disease (COPD). Liuzijue Qigong had positive effects on improving lung function, exercise capacity, health status, mental status, and quality of life in COPD patients. Liuzijue Qigong may be an effective adjuvant therapy for patients with COPD.